2016
DOI: 10.1016/j.memsci.2016.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Tri-bore PVDF hollow fibers with a super-hydrophobic coating for membrane distillation

Abstract: Membranes with good mechanical strength, high vapor flux and outstanding anti-wetting properties are essential for membrane distillation (MD) applications. In this work, porous polyvinylidene fluoride (PVDF) tri-bore hollow fiber membranes with super-hydrophobicity are developed to achieve these desired properties. The tri-bore hollow fiber offers better mechanical strength than the conventional single-bore fiber. To improve its anti-wetting properties, Teflon ® AF 2400 is coated on the membrane surface. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 44 publications
2
51
0
Order By: Relevance
“…Due to their superior tensile properties, multibore membranes have found their way into many applications such as drinking water production and seawater desalination [1,2,5], and wastewater and surface water filtration (direct contact membrane distillation [3,6,7] and vacuum membrane distillation [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their superior tensile properties, multibore membranes have found their way into many applications such as drinking water production and seawater desalination [1,2,5], and wastewater and surface water filtration (direct contact membrane distillation [3,6,7] and vacuum membrane distillation [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…They found that by changing the content of the particles can be increased the water contact angle of the membrane surface. Lu and coworker have used porous PVDF tri‐bore hollow fiber membrane for membrane distillation and then have coated Teflon AF2400 on the membrane surface to improve its antiwetting properties. The obtained membranes exhibited high flux without an occurrence of pore wetting.…”
Section: Introductionmentioning
confidence: 99%
“…There are several parameters that positively contribute to the success of the coating [25][26][27]: (i) the PP hollow fibers employed as support; its roughness facilitated the immobilization of ECTFE, its hydrophobicity facilitated the adhesion with the coating agent, whereas the chemical and thermal stability of PP ensured the survival of the hollow fibers from the harsh condition of the dip-coating; (ii) the excellent film-forming properties of ECTFE allowed the preparation of homogeneous coatings for the preparation of the protection layers; (iii) the solvent NMP facilitated the solubility of ECTFE at low temperature and enabled the preparation of polymeric ECTFE solution that quickly underwent demixing as a consequence of decreasing temperature of a few degrees, thus facilitating the Figure 3c); it can be seen that novel composite membranes present a less porous surface than PP hollow-fibers as a consequence of the deposition of ECTFE on the PP membrane support during the dip-coating process. This effect was also observed using the most diluted ECTFE polymeric solution (1 wt % of ECTFE).…”
Section: Ectfe/pp Composite Hollow Fibermentioning
confidence: 99%
“…In fact, ECTFE/PP composite membranes prepared using diluted concentration of ECTFE and short time of treatment (i.e., dip-coating) exhibited a hierarchical structure made of valleys entrapping air forming a gas-liquid interface with the feed solution, and resulting in a highly hydrophobic surface [25][26][27]. On the other hand, the hierarchical structure disappeared on increasing the concentration of ECTFE and time of dip-coating led to less porous and smoother surfaces with lower hydrophobic character.…”
Section: Ectfe (Wt%)mentioning
confidence: 99%